Utilization of Rice Husks as Green Amorphous Silica with Variations in the Addition of Sulfuric Acid and Citric Acid in the Acidification Process - Marta Pramudita; Rosmiati Rosmiati; Mahulia Hasriyati; Widya Ernayatie; Alia Badra Pitaloka (World Chemical Engineering Journal, 2026)
The acidification step in silica extraction from rice husks typically uses strong mineral acids, such as sulfuric acid, which pose safety risks and environmental concerns. Citric acid, a weak organic acid, is a safer and more environmentally friendly alternative for this process. This study aimed to produce green amorphous silica (GAS) from rice husk waste using the sol-gel method and to compare the effects of sulfuric acid and citric acid during the acidifying step. Rice husks were calcined at 700°C, acid-pretreated to pH 1, extracted with 1 M NaOH, and neutralized with either 1 M H₂SO₄ or 1 M C₆H₈O₇. The resulting silica powders were characterized using XRF, XRD, SEM-EDX, and FTIR. The SiO₂ content reached 95.22 % by mass with sulfuric acid and 93.59 % with citric acid. XRD revealed that sulfuric acid produced a poorly crystalline phase, whereas citric acid maintained a fully amorphous structure. SEM images showed uniform nanoparticles (~50–80 nm) for the sulfuric acid route, whereas citric acid produced more agglomerated clusters. FTIR spectra confirmed the presence of siloxane bonds in both samples; however, citric acid-derived silica exhibited residual carboxylate bands and less extensive condensation. Overall, sulfuric acid produced purer, more uniform silica suitable for high-performance applications. In contrast, citric acid proved a viable, greener alternative for preserving the amorphous state, suggesting that further process optimization could enhance its competitiveness in sustainable silica synthesis.